1979
DOI: 10.1002/jso.2930120311
|View full text |Cite
|
Sign up to set email alerts
|

5‐FU versus combination therapy with tubercidin, streptozotocin, and 5‐Fu in the treatment of pancreatic carcinomas: COG protocol 7230

Abstract: From May 1972 until May 1976, 105 patients were entered on Central Oncology Group protocol 7230 to compare the combination of streptozotocin, tubercidin, and 5-fluorouracil (5-FU) versus 5-FU alone in the treatment of adenocarcinoma and islet cell carcinoma of the pancreas. Twenty-nine were not evaluable. Thirty-six evaluable cases received 5-FU, and 40 received the combination, with no significant difference in time to progression or survival. Toxicity in the two regimens was somewhat different but was essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…5‐Fluorouracil (5‐FU) has also been in common use for the treatment of various cancers. Its effectiveness for the treatment of malignant neuroendocrine tumors seems to be similar to that observed with other gastrointestinal malignant tumors (i.e., pancreatic cancer) 15,16. The most intensively studied combined chemotherapy regimen for malignant neoendocrine tumors has been that of 5‐FU and streptozotocin, with results showing about 60% response rate 17,18…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…5‐Fluorouracil (5‐FU) has also been in common use for the treatment of various cancers. Its effectiveness for the treatment of malignant neuroendocrine tumors seems to be similar to that observed with other gastrointestinal malignant tumors (i.e., pancreatic cancer) 15,16. The most intensively studied combined chemotherapy regimen for malignant neoendocrine tumors has been that of 5‐FU and streptozotocin, with results showing about 60% response rate 17,18…”
Section: Discussionsupporting
confidence: 56%
“…Its effectiveness for the treatment of malignant neuroendocrine tumors seems to be similar to that observed with other gastrointestinal malignant tumors (i.e., pancreatic cancer). 15,16 The most intensively studied combined chemotherapy regimen for malignant neoendocrine tumors has been that of 5-FU and streptozotocin, with results showing about 60% response rate. 17,18 The mechanism of action of DTIC as an antitumor agent is not yet completely understood, but probably includes an alkylating action and inhibition of DNA synthesis.…”
Section: Casementioning
confidence: 99%
“…In addition to its free radical activity, trimidox has been shown to prevent ischemia reperfusion injury in an isolated rabbit heart model [31]. Streptozotocin, on the other hand, is a non-myelosuppressive agent with potent antitumor activity against islet carcinomas and malignant carcinoids [13]. In view of frequent blood transfusions in individuals with severe sickle cell disease, iron overload has been a major concern.…”
Section: Discussionmentioning
confidence: 99%
“…In their in vivo studies, Pace et al observed that administration of didox to transgenic sickle cell mice and an anemic baboon resulted in high level of ␥-globin gene expression [11]. Streptozotocin, on the other hand, is an anti-neoplastic agent that has been in use in combination regimens in cancer chemotherapy [13,14]. One of the unique pharmacological properties of STZ is its antitumor activity without bone marrow toxicity [15].…”
Section: Introductionmentioning
confidence: 99%
“…Tubercidin, toyocamycin, sangivamycin and derivatives are bacteria-derived adenosine analogues with different effects on RNA and DNA, protein kinase C, microtubules, and nucleophosmin (NPM1) [ 214 , 215 , 216 , 217 , 218 ]. These have been used in small clinical trials, in the case of tubercidin with clinical efficacy [ 219 , 220 , 221 , 222 , 223 , 224 ]. Importantly, differential resistance to these nucleoside analogues has been described in vitro [ 225 ].…”
Section: Overview On the Pharmacodynamics Of Nucleobase And Nucleomentioning
confidence: 99%